Effectiveness of Implementing an Infant Positioning Tool on Patient Positioning in a Neonatal Intensive Care Unit - Barbara A. Smith; Jill Kellis; Jolene Kramer; Hayden L. Smith (Advances in Neonatal Care, 2026)
ABSTRACT Background: Neonate patients receiving care may benefit from postural alignment support in improving neurodevelopment, physiologic functioning, and stability. Purpose: To assess the effectiveness of an infant positioning tool on patient positioning in a neonatal intensive care unit (NICU). Methods: A pre–post study design was used at a NICU within a free-standing children's hospital located in the Midwestern United States. The study was based on the implementation of an infant positioning tool by nursing. Study personnel collected neonate positioning scores before and after the tool's implementation. The instrument includes score values from 0 to 12, with higher scores representing better positioning. An intent-to-treat design was used to evaluate change. The primary study outcome was the observed median improvement in positioning scores. Results: Study sample included 168 (51%) observations collected from 89 unique neonates during the preintervention period and 159 (49%) observations collected from 69 unique neonates during the postintervention period. The sample had a median gestational age of 36 weeks, and most patients were direct NICU admissions. Primary admitting diagnoses were related to respiratory distress or failure. Median neonate positioning scores were 8 (interquartile range: 6, 9) in the preintervention and 10 (interquartile range: 9, 11) in the postintervention period represented by an estimated 2.1 (95% CI: 1.6, 2.8) median point increase. Implications for Practice: Study revealed an observed improvement in NICU infant positioning scores after the implemented change. Literature indicates that long-term impacts could include multisystemic improvements including orthopedic alignment, neurologic development, sensory/vestibular development, respiratory status, and potential decreased length of stay.